Indicators of different outcomes after prolonged weaning - Michels-Zetsche, Julia D.; Röser, Evelyn; Ersöz, Hilal; Neetz, Benjamin; Dahlhoff, Jana C.; Joves, Biljana; Trinkmann, Frederik; Höger, Philipp; Kontogianni, Konstantina; Weissmann, Cornelia; Barre, Max; Fähndrich, Sebastian; et al. (Scientific reports, 2025)
The outcomes of prolonged weaning in a specialist weaning centre range from successful weaning to death. We aimed to identify indicators of the different outcomes. We analysed 915 patients who underwent prolonged weaning at Thoraxklinik Heidelberg from Dec. 2008 to Dec. 2023. 73.2% were successfully weaned, 36.1% without (3a) and 37.1% with subsequent non-invasive ventilation (3b). 20.2% were discharged with IMV (3cI) and 6.6% died (3cII). The length of stay was significantly longer in the group discharged with IMV. Patients in weaning category 3a had fewer comorbidities, also as cause of IMV and were less obese (each at least OR ≤ 0.6, p ≤ 0.02). IMV before admission in days was significantly shorter, FiO2 higher and pCO2 lower, although with a weak effect (OR between 1.014 and 0.971). Indicators of category 3b were younger age (weak effect, OR 0.977), BMI ≥ 30 kg/m2 (OR 2.470, p < 0,001), higher pCO2 (OR 1.044), cause of IMV AECOPD (OR 2.803), pre-diagnosis of COPD (OR 2.073) and nosocomial pneumonia (OR 1.857), whereas patients with malignancy (OR 0.438) and CIP (critical illness polyneuropathy, OR 0.523) were less likely to fall into this category. Indicators of category 3cI were duration of previous IMV with a weak effect (OR 1.006), neuromuscular disease as the cause of IMV (OR 6.023), restrictive thoracic disease (OR 2.330), renal insufficiency (OR 1.977) and CIP (OR 1.744), absence of nosocomial pneumonia (OR 0.366). Only BMI ≤ 20 kg/m2 (OR 3.611), renal insufficiency (OR 1.253) and pre-diagnosed malignancy (OR 1.785) were indicators of category 3cII. The relevant indicators from multivariate analyses were transferred into ROC (receiver operating characteristic) curves and show an acceptable AUC (area under curve) between 0.72 and 0.79 for each of the four outcomes. There are specific indicators for each weaning outcome and an early assessment of each patient’s individual risk profile can help plan further outpatient care, shorten length of stay in the ventilator weaning unit and generate capacities for other patients in need of prolonged weaning.
Gesehen am 02.02.2026